PENGARUH UKURAN PERUSAHAAN, UKURAN KANTOR AKUNTAN PUBLIK (KAP), RISIKO PERUSAHAAN DAN PROFITABILITAS TERHADAP FEE AUDIT PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Mitha Christina Ginting; Duma Megaria Elisabeth; Jou Immanuel Sianturi (Universitas Methodist Indonesia, 2022)
The purpose of this study is to assess partially and quantitatively the effect of company size, KAP size, company risk and profitability on the audit fees of banking companies listed on the Indonesia Stock Exchange (IDX). It's about testing and analyzing at the same time. This type of research is causal research using a sample of 17 banking companies listed on the Indonesia Stock Exchange from 2017 to 2020. The sample survey was conducted using the target sampling method. The data used is secondary data obtained from the website www.idx.co.id. The first data analysis process is the traditional assumption test, then the hypothesis is tested. The statistical method used is multiple linear regression analysis. Meanwhile, the results of this study indicate that company size, accounting firm size (KAP), company risk and profitability together have a significant influence on registered bank audit fees. Indonesia Stock Exchange 2017. 2020. In part, company size has a large positive impact on audit fees, Public Accounting Firm (KAP) size has a large positive impact on audit fees, and company risk has a large positive impact on audit fees. has a positive but negligible impact on profitability and profitability has a positive impact. This will affect the exam fee.